2015
DOI: 10.3923/ajbkr.2015.119.128
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cancer Activity of Brachyuran Crab Dromia dehaani (Rathbun, 1923)

Abstract: Marine chemotherapy is well recognized now a days and profound development has been achieved by researchers to deal with different molecular pathways of tumors. In the present study, anticancer activity of the hemolymph of brachyuran crab D. dehaani was assayed with standard MTT colorimetric procedure against a range of human cell lines viz., HepG2, HT-29, rhabdomyosarcoma and A549. Cell viability was evaluated by 3-(4, 5-Dimethyl-2-thiazolyl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay. Cytotoxicity was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…Similar previous studies have reported the antitumor effects of hemolymph in other crabs like Atergatis roseus & Eriphia verrucosa (Salama and Mona, 2018), Scylla serrata (Pramanik et al, 2010) and Dromia dehaani (Priya and Ravichandr, 2015a;RethnaPriya et al, 2019). These antiproliferative activities of hemolymph were attributed to glycoproteins such as lectins and hemocyanin with molecular weights of ~75 KDa.…”
Section: Discussionsupporting
confidence: 78%
“…Similar previous studies have reported the antitumor effects of hemolymph in other crabs like Atergatis roseus & Eriphia verrucosa (Salama and Mona, 2018), Scylla serrata (Pramanik et al, 2010) and Dromia dehaani (Priya and Ravichandr, 2015a;RethnaPriya et al, 2019). These antiproliferative activities of hemolymph were attributed to glycoproteins such as lectins and hemocyanin with molecular weights of ~75 KDa.…”
Section: Discussionsupporting
confidence: 78%